Preparation method of acid and alkali resistant regenerated yarn
By dissolving the waste cotton fibers with sodium sulfamate and phosphoric acid, blending them with silica sol and silicon carbonate whiskers, and finally plated with a metal titanium layer, the problem of insufficient resistance in the acid-base environment is solved, and the preparation of acid-base regeneration yarn is achieved, which improves the mechanical properties and service life of the yarn.
Patent Information
- Application Number
- CN202510154383.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-02-12
- Publication Date
- 2025-03-14
- Estimated Expiration
- 2045-02-12
AI Technical Summary
The existing textiles are updated quickly and have short service life of clothing, resulting in waste of resources and insufficient yarn resistance in acid and alkali environments.
A preparation method is adopted to dissolve waste cotton fibers by sodium sulfamate and phosphoric acid, and blend them with silica sol and silicon carbonate whiskers, and finally a metal titanium layer is plated on the surface of the fiber to form an acid-base-resistant regeneration yarn.
It achieves the improvement of the acid and alkali resistance and mechanical properties of the yarn, extends the service life of the yarn, and reduces resource waste.
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of textile fibers, in particular to a method for preparing acid- and alkali-resistant regenerated yarn. Background Art
[0002] As a necessity of life, the demand for textiles is gradually increasing with the increase in population. In the past two decades, global fiber production has nearly tripled, from 58 million tons in 2000 to 109 million tons in 2020, and it is expected to increase to 146 million tons by 2030. Under the influence of the fast fashion trend, the speed of textile renewal has accelerated, the service life of clothing has decreased, and most clothing is discarded after being worn a few times, resulting in a waste of resources. Summary of the invention
[0003] The purpose of the present invention is to provide a method for preparing acid-alkali resistant regenerated yarn to solve the problems existing in the prior art.
[0004] In order to solve the above technical problems, the present invention provides the following technical solutions: a method for preparing acid-alkali resistant regenerated yarn, comprising the following preparation steps: (1) Sodium hydroxide, sodium aminosulfonate and deionized water are mixed, stirred at 100-200 rpm for 20-40 min, cooled to -10--15°C, cotton fibers are added, and shearing is performed. After the solution is heated to room temperature, a 90 wt% phosphoric acid aqueous solution is added, and shearing is continued for 1-3 h, and then centrifuged at 9000-15000 rpm for 8-16 min, and then deionized water is continuously added and stirred until white flocs appear. The mixture is allowed to stand for 1-3 h, the supernatant is removed, and the remaining portion is centrifuged at 5000-8000 rpm for 8-16 min, filtered, and the solid is taken out and washed until the pH of the washing solution is 7-8, and dried at 30-60°C for 20-30 h to obtain regenerated cellulose; (2) Regenerated cellulose, ethanol and deionized water were mixed and placed in a water bath at 50°C, stirred at 120 rpm for 1-3 h, silica sol and silicon carbonate whiskers were added, and stirring was continued for 2-5 h, octyl polysiloxane was added, and stirring was continued for 3 h, and the pH of the solution was adjusted to 10 with sodium hydroxide, and then wet-spun into a 50 wt% ethanol aqueous solution coagulation bath, coagulated for 1-3 h, and stretched during the coagulation process, with a stretch ratio of 1.3-1.8, then taken out, rinsed with deionized water for 5-10 times, and stretched for the second time, with a stretch ratio of 1.1-1.4, and dried at 40-60°C for 3-5 h to obtain regenerated yarn; (3) Immerse the regenerated yarn in a sensitizing solution at 30-40°C for sensitization treatment for 10-18 minutes, remove it, wash it with deionized water for 3-8 times, and then immerse it in an activation solution at 30-40°C for activation treatment for 8-12 minutes, remove it, wash it with deionized water for 3-8 times, and obtain pretreated regenerated yarn; mix titanium sulfate, sodium hypophosphite, sodium citrate, ammonium chloride, and deionized water in a mass ratio of 4.5:2:4.5:5:300-500, adjust the solution pH to 8-9 with ammonia water, heat it to 90°C, add 1-10 times the mass of titanium sulfate to the pretreated regenerated yarn, perform chemical plating, stir it every 10 minutes, then remove it, wash it with deionized water for 3-8 times, and dry it at 40-60°C for 3-5 hours to obtain acid and alkali resistant regenerated yarn.
[0005] Furthermore, the preparation method of the cotton fiber in step (1) is as follows: the waste cotton fabric is cut into 1 cm×1 cm size, broken into fibers at 200-500 rpm, and dried at 45-75° C. for 15-30 hours.
[0006] Furthermore, the shear rate in step (1) is 100-500 rpm.
[0007] Furthermore, in step (1), the mass ratio of the sodium hydroxide, sodium sulfamate, deionized water, cotton fiber, and 90 wt % phosphoric acid aqueous solution is 3-8:0.1-0.5:150:5-10:80-100.
[0008] Furthermore, the preparation method of the silica sol in step (2) is as follows: nano-silica and ethanol are mixed in a mass ratio of 5:80-150, stirred at 500 rpm for 20-50 min, and the solution pH is adjusted to 9.5-11 with aqueous ammonia, heated to 40°C, and vinyltrimethoxysilane in an amount of 1.5-4 times the mass of the nano-silica is added, and ultrasonicated at 21 kHz for 100-200 min to obtain the obtained solution.
[0009] Furthermore, the process parameters of the wet spinning in step (2) are: needle aperture of 0.2-0.6 mm, and extrusion speed of 0.04-0.1 mL / min.
[0010] Furthermore, in step (2), the mass ratio of the regenerated cellulose, ethanol, deionized water, silica sol, silicon carbonate whisker and octyl polysiloxane is 5-10:70:50:100-200:0.5-2:0.1.
[0011] Furthermore, the preparation method of the sensitizing solution in step (3) is as follows: stannous chloride, deionized water, and 90 wt % hydrochloric acid aqueous solution are uniformly mixed in a mass ratio of 0.5:50:2.5 to obtain the sensitizing solution.
[0012] Furthermore, the preparation method of the activation solution in step (3) is as follows: palladium chloride, ethanol and deionized water are uniformly mixed in a mass ratio of 0.25:500:500 to obtain the activation solution.
[0013] Furthermore, the process parameters of the chemical plating in step (3) are as follows: acceleration voltage is 5 kV, acceleration current is 10 μA, working distance is 7 mm, and time is 30-70 min.
[0014] Compared with the prior art, the beneficial effects achieved by the present invention are: The regenerated yarn of the invention is prepared by dissolving waste cotton fiber in sequence with sodium aminosulfonate and phosphoric acid, then blending and spinning with silicon dioxide sol and silicon carbide whisker, and coating a metal layer on the surface thereof to achieve acid and alkali resistance and strong strength.
[0015] Firstly, sodium aminosulfonate is used to dissolve the waste cotton fibers under shearing action. Under low temperature environment, sodium hydroxide is first used to swell the cellulose. Mechanical shearing force is used to assist sodium aminosulfonate to penetrate between the cellulose molecular chains. The hydrogen bond structure of the cellulose molecules is then destroyed through the hydrogen bond donors and hydrogen bond acceptors in its structure, promoting the dissolution of high-polymer cellulose molecules with low accessibility in the cotton fiber molecules. Since the dissolution of cotton fibers is an exothermic process, when the solution temperature reaches room temperature, phosphoric acid is added. Under the continuous attack of shear force and protons ionized by phosphoric acid, the cellulose finally presents a positively charged structure. Combined with the destruction of intermolecular hydrogen bonds and the electrostatic repulsion of cations, the cellulose dissociates evenly, indirectly enhancing the mechanical properties of the silk thread and achieving a regeneration effect.
[0016] Secondly, silica sol, silicon carbide whiskers and regenerated cellulose are blended and modified. A large number of hydroxyl groups on the surface of cellulose react with the hydroxyl groups of the sol, so that the molecular chains of silica sol and cellulose are entangled together to form a uniform network structure, in which the silicon carbide whiskers are adsorbed by the negatively charged silica silica particles and form a coating layer on their surface, which increases the electrostatic repulsive potential energy between substances, thereby effectively preventing the agglomeration of whiskers, making the matrix structure more stable, and enhancing the mechanical properties of the matrix. By reducing the hydrophilic groups in cellulose, the hydrophobicity of the matrix is enhanced, and a rough structure is formed on the fiber surface. Thereby, it can prevent the harm of acid or alkali solution to achieve the effect of acid and alkali resistance. Then, secondary drawing is carried out in the spinning process, and the fiber shrinks under the condition of internal force to form a denser structure. In the drawing process, cellulose stretches under the action of tension, so that the silicon carbide whiskers form an ordered structure in the direction parallel to the fiber and increase the orientation of the fiber, which is beneficial to improve the mechanical properties of the fiber. Finally, sodium citrate forms a complex with titanium ions to form a metal titanium coating with good bonding force and density on the rough surface of the fiber, further improving the acid and alkali resistance and mechanical properties of the fiber. DETAILED DESCRIPTION
[0017] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.
[0018] In order to more clearly illustrate the method provided by the present invention, the following examples are used to describe in detail the test methods of various indicators of the acid and alkali resistant regenerated yarn prepared in the following examples are as follows: Acid and alkali resistance: Take the same size of the embodiment and the comparative example and refer to GB / T20102 to carry out acid resistance strength retention rate and alkali resistance strength retention rate tests respectively. The acid solution is 10wt% sulfuric acid aqueous solution, the alkali solution is 5wt% sodium hydroxide aqueous solution, the temperature is 30°C, and the time is 96h.
[0019] Mechanical properties: The same size of the embodiment and the comparative example were taken to test their strength according to GB / T14337.
[0020] Example 1; (1) Cut waste cotton fabric into 1 cm × 1 cm size, break it into fibers at 200 rpm, and dry it at 45 ° C for 15 hours to obtain cotton fiber; mix sodium hydroxide, sodium sulfamate, and deionized water, stir at 100 rpm for 20 minutes, cool to -10 ° C, add cotton fiber, and shear at a shear rate of 100 rpm. After the solution is heated to room temperature, add 90 wt% phosphoric acid aqueous solution, continue shearing for 1 hour, and then centrifuge at 9000 rpm for 8 minutes, then continue to add deionized water and stir until white floccules appear, let it stand for 1 hour, pour off the supernatant, centrifuge the remaining part at 5000 rpm for 8 minutes, filter, take solid, wash until the pH of the washing liquid is 7, and dry at 30 ° C for 20 hours to obtain regenerated cellulose; the mass ratio of sodium hydroxide, sodium sulfamate, deionized water, cotton fiber, and 90 wt% phosphoric acid aqueous solution is 3:0.1:150:5:80; (2) Nano-silica and ethanol were mixed in a mass ratio of 5:80, stirred at 500 rpm for 20 min, and the pH of the solution was adjusted to 9.5 with ammonia water. The temperature was raised to 40°C, and vinyl trimethoxy silane (1.5 times the mass of the nano-silica) was added. Ultrasound was applied at 21 kHz for 100 min to obtain silica sol. Regenerated cellulose, ethanol, and deionized water were mixed, placed in a 50°C water bath, stirred at 120 rpm for 1 h, silica sol and silicon carbonate whiskers were added, and stirring was continued for 2 h. Octyl polysiloxane was added, and stirring was continued for 3 h. The solution pH was adjusted with sodium hydroxide. H is 10, and then wet spinning, the process parameters are: needle aperture of 0.2mm, extrusion speed of 0.04mL / min, to 50wt% ethanol aqueous solution coagulation bath, coagulation for 1h, and drawing during the coagulation process, the drawing ratio is 1.3, then fished out, rinsed with deionized water 5 times, and drawn for the second time, the drawing ratio is 1.1, and dried at 40℃ for 3h to obtain regenerated yarn; the mass ratio of regenerated cellulose, ethanol, deionized water, silica sol, silicon carbonate whisker, and octyl polysiloxane is 5:70:50:100:0.5:0.1; (3) Mix stannous chloride, deionized water, and 90 wt% hydrochloric acid aqueous solution at a mass ratio of 0.5:50:2.5 to obtain a sensitizing solution; mix palladium chloride, ethanol, and deionized water at a mass ratio of 0.25:500:500 to obtain an activation solution; immerse the regenerated yarn in the sensitizing solution at 30°C for 10 min, remove it, wash it with deionized water 3 times, and then immerse it in the activation solution at 30°C for 8 min, remove it, and wash it with deionized water 3 times to obtain the pretreated regenerated yarn yarn; titanium orthosulfate, sodium hypophosphite, sodium citrate, ammonium chloride and deionized water are mixed in a mass ratio of 4.5:2:4.5:5:300, the pH value of the solution is adjusted to 8 with ammonia water, the temperature is raised to 90°C, and 1 times the mass of titanium orthosulfate is added to the pretreated regenerated yarn for chemical plating. The process parameters are as follows: an accelerating voltage of 5 kV, an accelerating current of 10 μA, a working distance of 7 mm, a time of 30 min, and stirring every 10 min, then the yarn is taken out, washed 3 times with deionized water, and dried at 40°C for 3 h to obtain acid and alkali resistant regenerated yarn.
[0021] Example 2; (1) Cut waste cotton fabric into 1 cm × 1 cm size, break it into fibers at 350 rpm, and dry it at 60 ° C for 23 h to obtain cotton fiber; mix sodium hydroxide, sodium sulfamate, and deionized water, stir at 150 rpm for 30 min, cool to -13 ° C, add cotton fiber, and shear at a shear rate of 300 rpm. After the solution is heated to room temperature, add 90 wt% phosphoric acid aqueous solution, continue shearing for 2 h, and then centrifuge at 11000 rpm for 12 min, then continue to add deionized water and stir until white flocs appear, let it stand for 2 h, pour off the supernatant, centrifuge the remaining part at 6500 rpm for 12 min, filter, take solid, and wash until the pH of the washing liquid is 7.5, and dry at 45 ° C for 25 h to obtain regenerated cellulose; the mass ratio of sodium hydroxide, sodium sulfamate, deionized water, cotton fiber, and 90 wt% phosphoric acid aqueous solution is 6:0.3:150:7.5:90; (2) Nano-silica and ethanol were mixed in a mass ratio of 5:110, stirred at 500 rpm for 35 min, and the pH value of the solution was adjusted to 10 with aqueous ammonia. The temperature was raised to 40°C, and vinyltrimethoxysilane (3 times the mass of the nano-silica) was added. Ultrasound was performed at 21 kHz for 150 min to obtain silica sol. Regenerated cellulose, ethanol, and deionized water were mixed, placed in a 50°C water bath, stirred at 120 rpm for 2 h, silica sol and silicon carbonate whiskers were added, and stirring was continued for 3.5 h. Octyl polysiloxane was added, and stirring was continued for 3 h. The solution pH was adjusted with sodium hydroxide. H is 10, and then wet spinning, the process parameters are: needle aperture of 0.4mm, extrusion speed of 0.07mL / min, to 50wt% ethanol aqueous solution coagulation bath, coagulation for 2h, and drawing during the coagulation process, the drawing ratio is 1.5, then fished out, rinsed with deionized water 8 times, and drawn for the second time, the drawing ratio is 1.2, and dried at 50℃ for 4h to obtain regenerated yarn; the mass ratio of regenerated cellulose, ethanol, deionized water, silica sol, silicon carbonate whisker, and octyl polysiloxane is 8:70:50:150:1.25:0.1; (3) Mix stannous chloride, deionized water, and 90 wt% hydrochloric acid aqueous solution at a mass ratio of 0.5:50:2.5 to obtain a sensitizing solution; mix palladium chloride, ethanol, and deionized water at a mass ratio of 0.25:500:500 to obtain an activation solution; immerse the regenerated yarn in the sensitizing solution at 35°C for 14 minutes, remove it, wash it with deionized water 5 times, and then immerse it in the activation solution at 35°C for 10 minutes, remove it, and wash it with deionized water 5 times to obtain the pretreated regenerated yarn Titanium orthosulfate, sodium hypophosphite, sodium citrate, ammonium chloride and deionized water are mixed in a mass ratio of 4.5:2:4.5:5:400, the pH value of the solution is adjusted to 8.5 with ammonia water, the temperature is raised to 90°C, and 6 times the mass of pretreated regenerated yarn of titanium orthosulfate is added for chemical plating. The process parameters are as follows: acceleration voltage of 5 kV, acceleration current of 10 μA, working distance of 7 mm, time of 50 min, stirring every 10 min, then taking out and washing with deionized water for 5 times, and drying at 50°C for 4 h to obtain acid and alkali resistant regenerated yarn.
[0022] Example 3; (1) Cut waste cotton fabric into 1 cm × 1 cm size, break it into fibers at 500 rpm, and dry it at 75 ° C for 30 hours to obtain cotton fiber; mix sodium hydroxide, sodium sulfamate, and deionized water, stir at 200 rpm for 40 minutes, cool to -15 ° C, add cotton fiber, and shear at a shear rate of 500 rpm. After the solution is heated to room temperature, add 90 wt% phosphoric acid aqueous solution, continue shearing for 3 hours, and then centrifuge at 15000 rpm for 16 minutes, then continue to add deionized water and stir until white floccules appear, let it stand for 3 hours, pour off the supernatant, centrifuge the remaining part at 8000 rpm for 16 minutes, filter, take solid, wash until the pH of the washing liquid is 8, and dry at 60 ° C for 30 hours to obtain regenerated cellulose; the mass ratio of sodium hydroxide, sodium sulfamate, deionized water, cotton fiber, and 90 wt% phosphoric acid aqueous solution is 8:0.5:150:10:100; (2) Nano-silica and ethanol were mixed in a mass ratio of 5:150, stirred at 500 rpm for 50 min, and the pH value of the solution was adjusted to 11 with aqueous ammonia. The temperature was raised to 40°C, and vinyltrimethoxysilane (4 times the mass of the nano-silica) was added. Ultrasound was applied at 21 kHz for 200 min to obtain silica sol. Regenerated cellulose, ethanol, and deionized water were mixed, placed in a 50°C water bath, stirred at 120 rpm for 3 h, silica sol and silicon carbonate whiskers were added, and stirring was continued for 5 h. Octyl polysiloxane was added, and stirring was continued for 3 h. The solution pH was adjusted with sodium hydroxide. H is 10, and then wet spinning, the process parameters are: needle aperture of 0.6mm, extrusion speed of 0.1mL / min, to 50wt% ethanol aqueous solution coagulation bath, coagulation for 3h, and drawing during the coagulation process, the drawing ratio is 1.8, then fished out, rinsed with deionized water 10 times, and drawn for the second time, the drawing ratio is 1.4, and dried at 60℃ for 5h to obtain regenerated yarn; the mass ratio of regenerated cellulose, ethanol, deionized water, silica sol, silicon carbonate whisker, and octyl polysiloxane is 10:70:50:200:2:0.1; (3) Mix stannous chloride, deionized water, and 90 wt% hydrochloric acid aqueous solution at a mass ratio of 0.5:50:2.5 to obtain a sensitizing solution; mix palladium chloride, ethanol, and deionized water at a mass ratio of 0.25:500:500 to obtain an activation solution; immerse the regenerated yarn in the sensitizing solution at 40°C for 18 minutes, remove it, wash it with deionized water 8 times, and then immerse it in the activation solution at 40°C for 12 minutes, remove it, and wash it with deionized water 8 times to obtain the pretreated regenerated yarn yarn; titanium orthosulfate, sodium hypophosphite, sodium citrate, ammonium chloride and deionized water are mixed in a mass ratio of 4.5:2:4.5:5:500, the pH value of the solution is adjusted to 9 with ammonia water, the temperature is raised to 90°C, and 10 times the mass of the pretreated regenerated yarn of titanium orthosulfate is added for chemical plating. The process parameters are as follows: accelerating voltage of 5 kV, accelerating current of 10 μA, working distance of 7 mm, time of 70 min, stirring every 10 min, and then taking out and washing with deionized water for 8 times, and drying at 60°C for 5 h to obtain acid and alkali resistant regenerated yarn.
[0023] Comparative Example 1: The difference between Comparative Example 1 and Example 2 is that step (2) is different. Step (2) is changed to: regenerated cellulose, ethanol and deionized water are mixed, placed in a water bath at 50°C, stirred at 120rpm for 2h, silicon carbonate whiskers are added, stirring is continued for 3.5h, octyl polysiloxane is added, stirring is continued for 3h, the pH of the solution is adjusted to 10 with sodium hydroxide, and then wet-spun, wherein the process parameters are: needle aperture of 0.4mm, extrusion speed of 0.07mL / min, put into a 50wt% ethanol aqueous solution coagulation bath, coagulate for 2h, and stretch during the coagulation process, with a stretch ratio of 1.5, then fish out, rinse with deionized water 8 times, stretch for the second time, with a stretch ratio of 1.2, and dry at 50°C for 4h to obtain regenerated yarn; the mass ratio of the regenerated cellulose, ethanol, deionized water, silicon carbonate whiskers and octyl polysiloxane is 8:70:50:1.25:0.1; the remaining steps are the same as those in Example 2.
[0024] Comparative Example 2: The difference between Comparative Example 2 and Example 2 is that step (2) is different, and step (2) is changed to: nano-silica and ethanol are mixed in a mass ratio of 5:110, stirred at 500rpm for 35min, and adjusted to a solution pH of 10 with ammonia water, heated to 40°C, and vinyltrimethoxysilane 3 times the mass of nano-silica is added, and ultrasonicated at 21kHz for 150min to obtain silica sol; regenerated cellulose, ethanol, and deionized water are mixed, placed in a 50°C water bath, stirred at 120rpm for 2h, silica sol is added, stirring is continued for 3.5h, octyl polysiloxane is added, and stirring is continued The mixture was stirred for 3 hours, and the pH value of the solution was adjusted to 10 with sodium hydroxide, and then wet-spun with the following process parameters: the needle diameter was 0.4 mm, the extrusion speed was 0.07 mL / min, and the mixture was put into a 50 wt% ethanol aqueous solution coagulation bath for coagulation for 2 hours. During the coagulation process, the mixture was stretched with a stretching ratio of 1.5, and then the mixture was taken out, rinsed with deionized water for 8 times, stretched for the second time with a stretching ratio of 1.2, and dried at 50°C for 4 hours to obtain regenerated yarn. The mass ratio of the regenerated cellulose, ethanol, deionized water, silica sol and octyl polysiloxane was 8:70:50:150:0.1. The remaining steps were the same as those in Example 2.
[0025] Comparative Example 3; The difference between Comparative Example 3 and Example 2 is that step (2) is different, and step (2) is changed to: nano-silicon dioxide and ethanol are mixed in a mass ratio of 5:110, stirred at 500rpm for 35min, and adjusted to a pH of 10 with ammonia water, heated to 40°C, and vinyltrimethoxysilane 3 times the mass of nano-silicon dioxide is added, and ultrasonicated at 21kHz for 150min to obtain silica sol; regenerated cellulose, ethanol, and deionized water are mixed, placed in a water bath at 50°C, stirred at 120rpm for 2h, and silica sol and silicon carbonate whiskers are added, and stirring is continued for 3 .5h, add octyl polysiloxane, stir for another 3h, adjust the solution pH to 10 with sodium hydroxide, and then wet-spin with the process parameters as follows: needle aperture of 0.4mm, extrusion speed of 0.07mL / min, put into 50wt% ethanol aqueous solution coagulation bath, coagulate for 2h, fish out, rinse with deionized water 8 times, dry at 50℃ for 4h to obtain regenerated yarn; the mass ratio of regenerated cellulose, ethanol, deionized water, silica sol, silicon carbonate whisker and octyl polysiloxane is 8:70:50:150:1.25:0.1; the remaining steps are the same as those in Example 2.
[0026] Comparative Example 4: The difference between Comparative Example 4 and Example 2 is that there is no step (3); the remaining steps are the same as Example 2.
[0027] Effect example Table 1 below shows the performance analysis results of the acid- and alkali-resistant regenerated yarns of Examples 1 to 3 of the present invention and Comparative Examples 1 to 4.
[0028] Table 1
[0029] From the comparison of the experimental results of the embodiment and the comparative example in Table 1, it can be found that the present invention utilizes silica sol, silicon carbide whiskers and regenerated cellulose for blending and modification, so that the molecular chains of silica sol and cellulose are entangled together to form a uniform network structure, wherein the silicon carbide whiskers are adsorbed by the negatively charged silica gel particles and form a coating layer on the surface thereof, thereby increasing the electrostatic repulsion potential energy between the substances, thereby effectively preventing the agglomeration between the whiskers, making the matrix structure more stable, and enhancing the mechanical properties of the matrix, and by reducing the hydrophilic groups in the cellulose, the hydrophobicity of the matrix is enhanced, and a rough structure is formed on the fiber surface, thereby preventing the persecution of acid or alkali solution, then, secondary drawing is performed during the spinning process, the fiber shrinks under the condition of the internal force to form a relatively dense structure, and the silicon carbide whiskers form an ordered structure in a direction parallel to the fiber, thereby facilitating the improvement of the mechanical properties of the fiber, and finally, sodium citrate forms a complex with titanium ions, thereby forming a metal titanium coating with good bonding force and density on the rough surface of the fiber, further improving the acid and alkali resistance and mechanical properties of the fiber.
[0030] It will be apparent to those skilled in the art that the invention is not limited to the details of the exemplary embodiments described above and that the invention can be implemented in other specific forms without departing from the spirit or essential features of the invention. Therefore, the embodiments should be considered in all respects as exemplary and non-limiting, and the scope of the invention is defined by the appended claims rather than the foregoing description, and it is intended that all variations within the meaning and scope of the equivalent elements of the claims be included in the invention. Any marking in a claim should not be considered as limiting the claim to which it relates.
Claims
1. A method for preparing acid- and alkali-resistant regenerated yarn, characterized in that: The method comprises the following preparation steps: (1) Sodium hydroxide, sodium aminosulfonate and deionized water are mixed, stirred at 100-200 rpm for 20-40 min, cooled to -10--15°C, cotton fibers are added, and shearing is performed. After the solution is heated to room temperature, a 90 wt% phosphoric acid aqueous solution is added, and shearing is continued for 1-3 h, and then centrifuged at 9000-15000 rpm for 8-16 min, and then deionized water is continuously added and stirred until white flocs appear. The mixture is allowed to stand for 1-3 h, the supernatant is removed, and the remaining portion is centrifuged at 5000-8000 rpm for 8-16 min, filtered, and the solid is taken out and washed until the pH of the washing solution is 7-8, and dried at 30-60°C for 20-30 h to obtain regenerated cellulose; (2) Regenerated cellulose, ethanol and deionized water were mixed and placed in a water bath at 50°C, stirred at 120 rpm for 1-3 h, silica sol and silicon carbonate whiskers were added, and stirring was continued for 2-5 h, octyl polysiloxane was added, and stirring was continued for 3 h, and the pH of the solution was adjusted to 10 with sodium hydroxide, and then wet-spun into a 50 wt% ethanol aqueous solution coagulation bath, coagulated for 1-3 h, and stretched during the coagulation process, with a stretch ratio of 1.3-1.8, then taken out, rinsed with deionized water for 5-10 times, and stretched for the second time, with a stretch ratio of 1.1-1.4, and dried at 40-60°C for 3-5 h to obtain regenerated yarn; (3) Immerse the regenerated yarn in a sensitizing solution at 30-40°C for sensitization treatment for 10-18 minutes, remove it, wash it with deionized water for 3-8 times, and then immerse it in an activation solution at 30-40°C for activation treatment for 8-12 minutes, remove it, wash it with deionized water for 3-8 times, and obtain pretreated regenerated yarn; mix titanium sulfate, sodium hypophosphite, sodium citrate, ammonium chloride, and deionized water in a mass ratio of 4.5:2:4.5:5:300-500, adjust the solution pH to 8-9 with ammonia water, heat it to 90°C, add 1-10 times the mass of titanium sulfate to the pretreated regenerated yarn, perform chemical plating, stir it every 10 minutes, then remove it, wash it with deionized water for 3-8 times, and dry it at 40-60°C for 3-5 hours to obtain acid and alkali resistant regenerated yarn.
2. The method for preparing an acid- and alkali-resistant regenerated yarn according to claim 1, characterized in that: The preparation method of the cotton fiber in step (1) is as follows: the waste cotton fabric is cut into 1 cm×1 cm size, broken into fibers at 200-500 rpm, and dried at 45-75° C. for 15-30 hours.
3. The method for preparing an acid- and alkali-resistant regenerated yarn according to claim 1, characterized in that: The shear rate in step (1) is 100-500 rpm.
4. The method for preparing an acid- and alkali-resistant regenerated yarn according to claim 1, characterized in that: The mass ratio of the sodium hydroxide, sodium sulfamate, deionized water, cotton fiber and 90wt% phosphoric acid aqueous solution in step (1) is 3~8:0.1~0.5:150:5~10:80~100.
5. The method for preparing acid- and alkali-resistant regenerated yarn according to claim 1, characterized in that: The preparation method of the silica sol in step (2) is as follows: nano-silica and ethanol are mixed in a mass ratio of 5:80-150, stirred at 500 rpm for 20-50 min, and the solution pH is adjusted to 9.5-11 with aqueous ammonia, heated to 40° C., and vinyltrimethoxysilane in an amount of 1.5-4 times the mass of the nano-silica is added, and ultrasonicated at 21 kHz for 100-200 min to obtain the obtained solution.
6. The method for preparing acid- and alkali-resistant regenerated yarn according to claim 1, characterized in that: The process parameters of the wet spinning in step (2) are: needle aperture of 0.2-0.6 mm, and extrusion speed of 0.04-0.1 mL / min.
7. The method for preparing acid- and alkali-resistant regenerated yarn according to claim 1, characterized in that: The mass ratio of the regenerated cellulose, ethanol, deionized water, silica sol, silicon carbonate whisker and octyl polysiloxane in step (2) is 5-10:70:50:100-200:0.5-2:0.
1.
8. The method for preparing acid- and alkali-resistant regenerated yarn according to claim 1, characterized in that: The preparation method of the sensitizing solution in step (3) is as follows: stannous chloride, deionized water, and 90 wt% hydrochloric acid aqueous solution are uniformly mixed in a mass ratio of 0.5:50:2.5 to obtain the sensitizing solution.
9. The method for preparing acid- and alkali-resistant regenerated yarn according to claim 1, characterized in that: The preparation method of the activation solution in step (3) is as follows: palladium chloride, ethanol and deionized water are uniformly mixed in a mass ratio of 0.25:500:500 to obtain the activation solution.
10. The method for preparing acid- and alkali-resistant regenerated yarn according to claim 1, characterized in that: The process parameters of the chemical plating in step (3) are as follows: acceleration voltage of 5 kV, acceleration current of 10 μA, working distance of 7 mm, and time of 30 to 70 min.
Citation Information
Patent Citations
Flame retardant nonwoven fabric and bedding articles
CN101956298A
Regenerated cellulosic fibers spun from an aqueous alkaline spindope
CN110621701A
Crease-resistant arc-proof fabric and preparation method thereof
CN115418850A